1999
DOI: 10.1177/0095798499025002002
|View full text |Cite
|
Sign up to set email alerts
|

Racial Identity and Racial Socialization Attitudes of African American Parents

Abstract: This study explores racial socialization messages used by African American parents, specific messages according to the gender of children, and the relationship between racial socialization and racial identity attitudes as measured by the Racial Identity Attitude Scale. One hundred four African American parents participated in the study. Racial socialization was seen as important to the vast majority of parents and they reported a wide variety of socialization messages. Chi-square analysis suggests that message… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
194
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(215 citation statements)
references
References 33 publications
18
194
3
Order By: Relevance
“…Black girls are targeted for collectivist themes concerning racial pride and unity; in contrast, black males are sent messages oriented to the struggles of individuals to overcome discrimination to achieve equality (Thomas & Speight, 1999). Black mothers are also more firm with daughters than with sons.…”
Section: Story Themes and Self-construalmentioning
confidence: 99%
“…Black girls are targeted for collectivist themes concerning racial pride and unity; in contrast, black males are sent messages oriented to the struggles of individuals to overcome discrimination to achieve equality (Thomas & Speight, 1999). Black mothers are also more firm with daughters than with sons.…”
Section: Story Themes and Self-construalmentioning
confidence: 99%
“…In addition, racial identity status has been associated with, and predictive of, how African Americans manage painful affect (Neveill, Heppner, & Wang, 1997;Wilson & Constatine, 1999), aggression (DeCarlo, 2001 this study), levels of internal locus of control (Jackson & Neville, 1998), and general psychological functioning (Loo, Fair bank, & Scurfield king, 1999). For adolescents, poor identity has also been related to low selfesteem, low school achievement, school drop out, teenage pregnancy, gang involvement, eating disorders and drug abuse, (Cross, 1991;Thomas & Speight, 1999). Hence, social workers who have an informed understanding of the identity development process of African American adolescents have a greater chance of being a more effective interventionist.…”
Section: Identity and Social Work Interventionmentioning
confidence: 99%
“…Racial/ethnic pride and family/community empowerment themes have been shown to be effective methods of reducing symptoms related to key psychiatric disorders (CDC, 1999;Neighbors, Braithwaite, & Thompson, 1995;Thomas & Speight, 1999). However, the key conclusion of this study highlights the importance of acknowledging within-group heterogeneity in investigations of patterns of behaviors that may be related to levels of racial identity salience.…”
Section: Practice-related Implicationsmentioning
confidence: 82%
“…Studies have documented that school (e.g., Kerwin & Ponterotto, 1995;Pope, 2000;Shelton & Sellers, 2000), peer (e.g., Plummer, 1995;Thompson, 1994), and family environments (e.g., McRoy & Zurcher, 1983;Peters, 1985;Thomas & Speight, 1999) all contribute directly and indirectly to the manner by which individuals come to identify themselves racially and ethnically. For example, an emerging research literature has suggested that through parental interaction, Black parents communicate to their children racially relevant thoughts, values, and attitudes (e.g., how to deal with racial bias and discrimination) that help youth navigate their social environments (Demo & Hughes, 1990;Hughes, 2003).…”
Section: Racial Identity Developmentmentioning
confidence: 99%